2020
DOI: 10.1038/s41586-020-2700-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in immune responses that underlie COVID-19 disease outcomes

Abstract: CLIA-certified laboratories were enrolled through the IMPACT biorepository study 15. In the IMPACT study, biospecimens including blood, nasopharyngeal swabs, saliva, urine and stool samples were collected at study enrolment (baseline denotes the first time point) and longitudinally on average every 3 to 7 days (serial time points). The detailed demographics and clinical characteristics of these 98 participants are shown in Extended Data Table 1. Plasma and peripheral blood mononuclear cells (PBMCs) were isolat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

96
1,007
25
26

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,196 publications
(1,208 citation statements)
references
References 20 publications
96
1,007
25
26
Order By: Relevance
“…Translational studies in adult COVID-19 identified T cell lymphopenia in particular, with a preferential decrease in CD8 T cells compared to CD4 T cells [21][22][23] . In those lymphocytes remaining, marked activation of CD4 and CD8 T cells was observed, and T cell activation correlated positively with severity of illness 22,[24][25][26][27][28] . However, even among the sickest adults, the degree of immune activation varies 22,24,25,29 .…”
Section: Introductionmentioning
confidence: 98%
“…Translational studies in adult COVID-19 identified T cell lymphopenia in particular, with a preferential decrease in CD8 T cells compared to CD4 T cells [21][22][23] . In those lymphocytes remaining, marked activation of CD4 and CD8 T cells was observed, and T cell activation correlated positively with severity of illness 22,[24][25][26][27][28] . However, even among the sickest adults, the degree of immune activation varies 22,24,25,29 .…”
Section: Introductionmentioning
confidence: 98%
“…Another factor to consider is whether the sex of the patient affects the level of inflammatory mediators such as cytokines in the body. Although a study illustrates there is a similar level of IL-8 and IL-18 between males and females who have severe SARS-CoV-2 infections, this is not concordant with other findings in the study (30). For example, the concentration of IFNA2 is higher in females, however levels of CCL5 are more elevated in males during the pathogenesis of the disease (30).…”
Section: Cytokine Storm: the Hyperactivity Of Cytokinesmentioning
confidence: 59%
“…Gender speci c analysis showed that the T cell-induced upregulation of CD123 on monocytes was signi cantly higher in healthy males and non-ventilated male patients than in the same groups of females. As IL-3 contributes to activation of monocytes 33 , the stronger T cell -monocyte link in males may explain the recently described higher plasma levels of IL-8 and IL-18 in male COVID-19 patients 34 .…”
Section: Discussionmentioning
confidence: 95%